2013
DOI: 10.1159/000350588
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody against α-Actinin 4 from Human Umbilical Vein Endothelial Cells Inhibits Endothelium-Dependent Vasorelaxation

Abstract: Background: This study was attempted to identify new molecules expressed on the plasma membrane of human umbilical vein endothelial cells (HUVECs) using monoclonal antibody-based proteomics technology and to determine the effect of the identified antibody on vascular reactivity. Methods: Twenty-two antibodies were developed from rats inoculated with HUVECs, and their effects were determined by observing vascular reactivity. Results: Among the 22 antibodies, the C-7 antibody significantly inhibited endothelium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…To further investigate another monoclonal antibody associated with vascular function, we tested the effects of antibodies with specific reactivity to HUVECs other than the antibody (C7) with vascular reactivity, which is one of the seven antibodies exhibiting more than 80% specific reactivity to HUVECs in a previous study. Among the different antibodies, A-7 displayed 45.9% specific reactivity to HUVEC as reported previously (Won et al 2013) and affected vascular reactivity as shown in Figure 1. Treatment of ACh (0.01-1 μM) elicited concentration-dependent inhibition of NE (0.1 μM)-induced contraction in endothelium-intact aortic ring isolated from rats, with a maximum inhibition at 1 μM of ACh (Figure 1; n = 4).…”
Section: Effect Of A-7 Antibody On Endothelium-dependent Vasorelaxationsupporting
confidence: 72%
See 4 more Smart Citations
“…To further investigate another monoclonal antibody associated with vascular function, we tested the effects of antibodies with specific reactivity to HUVECs other than the antibody (C7) with vascular reactivity, which is one of the seven antibodies exhibiting more than 80% specific reactivity to HUVECs in a previous study. Among the different antibodies, A-7 displayed 45.9% specific reactivity to HUVEC as reported previously (Won et al 2013) and affected vascular reactivity as shown in Figure 1. Treatment of ACh (0.01-1 μM) elicited concentration-dependent inhibition of NE (0.1 μM)-induced contraction in endothelium-intact aortic ring isolated from rats, with a maximum inhibition at 1 μM of ACh (Figure 1; n = 4).…”
Section: Effect Of A-7 Antibody On Endothelium-dependent Vasorelaxationsupporting
confidence: 72%
“…Male Sprague-Dawley (SD) rats (7-weeks-old, 180-190 g, n = 10) were purchased from Orient Bio (Korea). The animals were euthanized using CO 2 gas inhalation and bled rapidly by severing the carotid arteries (Won et al 2013;Raffetto et al 2019). The thoracic aorta was rapidly and carefully removed and placed in a physiological salt solution (PSS) containing the following composition (in mM): NaCl 136.9; KCl 5.4; CaCl 2 1.5; MgCl 2 1.0; NaHCO 3 23.8; EDTA 0.01.…”
Section: Tissue Preparation and Measurement Of Isometric Contractionmentioning
confidence: 99%
See 3 more Smart Citations